Exogenous Histamine Stimulates Colorectal Cancer Implant Growth via Immunosuppression in Mice - Kazuyoshi Tomita; Susumu Okabe (Elsevier, 2005)
Results from a limited number of studies suggest a potential role for endogenous histamine in regulating tumor growth in immunocompetent cells. The present study examined the effects of exogenous histamine on colorectal cancer growth and the immune response against tumor tissue in mice. Histamine was administered for 21 days to Colon 38 mouse colon adenocarcinoma-implanted syngeneic mice and tumor volume was measured throughout the experiment. Systemic administration of histamine for 21 days caused a significant increase in tumor implant growth compared with the vehicle. At the end of histamine administration, the interferon (IFN)-γ / interleukin (IL)-4 ratio in peripheral lymphocytes, as well as histamine and cytokine levels in tumor implants were determined. Histamine levels in tumor implants remained unchanged after exogenous histamine delivery. Mice with tumor implants exhibited significantly elevated IFN-γ / IL-4 ratios compared with mice lacking tumors. Nonetheless, the increased IFN-γ / IL-4 ratios were markedly suppressed by histamine administration compared with vehicle. In addition, histamine delivery significantly decreased IFN-γ and IL-12 mRNA expression, but increased IL-10 mRNA expression in tumor implants. It was concluded that exogenous histamine dysregulates the balance between T-helper 1 (Th1) and T-helper 2 (Th2) cells, attenuating anti-tumor cytokine expression in the tumor microenvironment, thus resulting in stimulated colorectal cancer growth. Keywords:: tumor growth, Th1/Th2 balance, interferon-γ, interleukin-12, interleukin-10